lens

JP7635538B2Active Publication Date: 2025-02-26DIC CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020199466
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-01
Publication Date
2025-02-26
Estimated Expiration
2040-12-01

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、樹脂層及び無機層を有する積層体において、無機層のクラック発生を抑制可能な優れた耐クラック性を有する樹脂層形成用活性エネルギー線硬化性樹脂組成物、前記活性エネルギー線硬化性樹脂組成物の硬化物、積層体及び前記積層体からなるレンズを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635538000001
    Figure 0007635538000001
  • Figure 0007635538000002
    Figure 0007635538000002
Patent Text Reader

Abstract

To provide an active energy ray curable resin composition for resin layer formation which has an excellent crack resistance capable of suppressing crack occurrence on an inorganic layer, in a laminate having a resin layer and the inorganic layer, a cured object of the active energy ray curable resin composition, a laminate and a lens formed of the laminate.SOLUTION: The invention provides an active energy ray curable resin composition comprising: (A) a multi-branched polymer compound comprising a multi-branch structure and 6 or more (meth)acryloyl groups, in one molecule; and (B) aliphatic urethane (meth)acrylate. By use of the active energy ray curable resin composition, the problem can be solved.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active energy ray-curable resin composition for forming a resin layer of a laminate having a resin layer and an inorganic layer, a cured product of the active energy ray-curable resin composition, a laminate, and a lens comprising the laminate. [Background technology]

[0002] In recent years, curable resin compositions, such as active energy ray-curable resin compositions that can be cured by active energy rays such as ultraviolet rays and thermosetting resin compositions that can be cured by heat, have been widely used in the fields of inks, paints, coating agents, adhesives, optical components, and the like. In particular, in the field of optical components, they are suitably used as lens resins for smartphones and car-mounted cameras. As a molding method for the lens resins, a manufacturing process using optical imprinting has been actively studied because it leads to thinner lens modules and improved production efficiency. The optical imprinting method is a method in which an uncured resin is applied to a substrate such as a wafer, and then the substrate is sandwiched between lens molds to transfer the shape, and then photocured, thereby enabling the molding of hundreds of wafer-level lenses at once.

[0003] As a resin used for the photoimprinting, a curable resin composition containing urethane (meth)acrylate is known (see, for example, Patent Document 1). However, when the upper layer of the lens is covered with an anti-reflective film after the lens is molded, there are problems such as the occurrence of cracks.

[0004] Therefore, there has been a demand for a material for forming a resin layer that can suppress the occurrence of cracks in an inorganic layer after the formation of the inorganic layer, such as an anti-reflection film. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2019 / 142061 Summary of the Invention [Problem to be solved by the invention]

[0006] The problem to be solved by the present invention is to provide an active energy ray-curable resin composition for forming a resin layer, which has excellent crack resistance capable of suppressing cracking in the inorganic layer in a laminate having a resin layer and an inorganic layer, a cured product of the active energy ray-curable resin composition, a laminate, and a lens comprising the laminate. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that the above problems can be solved by using an active energy ray-curable resin composition containing a hyperbranched polymer compound (A) having a hyperbranched structure and six or more (meth)acryloyl groups in one molecule, and an aliphatic urethane (meth)acrylate (B), thereby completing the present invention.

[0008] That is, the present invention relates to an active energy ray-curable resin composition for forming a resin layer of a laminate having a resin layer and an inorganic layer, the active energy ray-curable resin composition comprising a compound (A) having six or more (meth)acryloyl groups and a multi-branched structure in one molecule, and an aliphatic urethane (meth)acrylate (B); a cured product of the active energy ray-curable resin composition; a laminate; and a lens comprising the laminate. Effect of the Invention

[0009] According to the present invention, it is possible to provide an active energy ray-curable resin composition for forming a resin layer having excellent crack resistance capable of suppressing cracking in the inorganic layer in a laminate having a resin layer and an inorganic layer, a cured product of the active energy ray-curable resin composition, a laminate, and a lens comprising the laminate.

[0010] Furthermore, since the active energy ray-curable resin composition of the present invention can suppress the occurrence of cracks in the inorganic layer in a laminate having a resin layer and an inorganic layer, it can be suitably used in lens production by photoimprinting. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The active energy ray-curable resin composition of the present invention is characterized by containing a hyperbranched polymer compound (A) having a hyperbranched structure and six or more (meth)acryloyl groups in one molecule, and an aliphatic urethane (meth)acrylate (B).

[0012] In the present invention, "(meth)acryloyl" means acryloyl and / or methacryloyl. "(meth)acrylate" means acrylate and / or methacrylate. "(meth)acrylic" means acrylic and / or methacrylic.

[0013] Examples of the hyperbranched polymer compound (A) having a hyperbranched structure and six or more (meth)acryloyl groups in one molecule include a compound having a dendrimer structure (branched structure) (hereinafter sometimes referred to as a "dendrimer"), a compound having a hyperbranched structure (hereinafter sometimes referred to as a "hyperbranch" or "hyperbranched polymer"), a compound having a star structure, and the like, and are not particularly limited as long as the effects of the present invention can be obtained.

[0014] Examples of commercially available products of the compound having a dendrimer structure include "Viscoat #1000LT" manufactured by Osaka Organic Chemical Industry Co., Ltd. and "Miramer SP1106" manufactured by MIWON Co., Ltd. These compounds having a dendrimer structure can be used alone or in combination of two or more kinds.

[0015] Examples of commercially available products of the compound having the hyperbranched structure include "CN2302", "CN2303", and "CN2304" manufactured by Arkema, and "Photomer 5500" manufactured by IGM. These compounds having a hyperbranched structure can be used alone or in combination of two or more kinds.

[0016] The multi-branched polymer compound (A) contains a compound having 6 or more (meth)acryloyl groups in its structure. The average number of (meth)acryloyl groups contained in one molecule of the multi-branched polymer compound is more preferably in the range of 6 to 64, since an active energy ray-curable resin composition having excellent crack resistance capable of suppressing crack generation in the inorganic layer can be obtained, and particularly preferably in the range of 10 to 32, since the crack generation suppression effect is remarkable.

[0017] The weight average molecular weight (Mw) of the hyperbranched polymer compound (A) is preferably in the range of 500 to 30,000 since an active energy ray-curable resin composition having excellent crack resistance capable of suppressing crack generation in the inorganic layer can be obtained, and more preferably in the range of 1,000 to 10,000 since the crack generation suppression effect becomes significant. In the present invention, the weight average molecular weight (Mw) indicates a value measured by gel permeation chromatography (GPC).

[0018] The viscosity of the hyperbranched polymer compound (A) at 25° C. is preferably in the range of 10 mPa·s to 1,500 mPa·s, and more preferably in the range of 100 mPa·s to 1,000 mPa·s. In the present invention, the viscosity is a value measured by an E-type viscometer.

[0019] The method for producing the multi-branched polymer compound (A) is not particularly limited, and can be produced by a known method as appropriate. For example, the divergent method in which a molecule is bonded to a central core molecule for each generation to form a branch, the convergent method in which a branch portion synthesized in advance is bonded to a core molecule, and a method of synthesis in one step using a monomer ABx having a branch portion having two or more reaction points B and a linking portion having another reaction point A in one molecule are listed. Among them, the divergent method is preferred, and for example, the multi-branched polymer compound (A) is preferably produced by a method in which a polyhydric alcohol and a compound having one or more carboxyl groups and two or more hydroxyl groups are esterified to obtain a multi-branched polyester polyol, and then the terminal hydroxyl group is reacted with (meth)acrylic acid.

[0020] Examples of the polyhydric alcohol include glycerin, trimethylolpropane, ditrimethylolpropane, trimethylolethane, ditrimethylolethane, tris(2-hydroxyethyl)isocyanurate, 1,2,4-butanetriol, pentaerythritol, dipentaerythritol, sorbitol, mannitol, and alkylene oxide adducts or caprolactone adducts thereof. These polyhydric alcohols can be used alone or in combination of two or more kinds.

[0021] Examples of the compound having one or more carboxyl groups and two or more hydroxyl groups include 2,3-dihydroxypropionic acid, 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, tartaric acid, 2,3-dihydroxybenzoic acid, 2,4-dihydroxybenzoic acid, 2,5-dihydroxybenzoic acid, 2,6-dihydroxybenzoic acid, 3,4-dihydroxybenzoic acid, 3,5-dihydroxybenzoic acid, 3,5-bis(2-hydroxyethoxy)benzoic acid, 2,6-dihydroxy-4-methylbenzoic acid, 3,5-dihydroxy-4-methylbenzoic acid, citrazinic acid, 2,3-dihydroxyphenylacetic acid, 2,4-dihydroxyphenylacetic acid, 2,5-dihydroxyphenylacetic acid, 2,6-dihydroxyphenylacetic acid, 3,4-dihydroxyphenylacetic acid, 3,5-dihydroxyphenylacetic acid, and derivatives thereof. These compounds can be used alone or in combination of two or more kinds.

[0022] As the hyperbranched polyester polyol, as described above, in addition to being obtained by subjecting a polyhydric alcohol to an esterification reaction with a compound having one or more carboxyl groups and two or more hydroxyl groups, a commercially available product can also be used.

[0023] Commercially available hyperbranched polyester polyols include, for example, "BOLTORN H20", "BOLTORN H30", "BOLTORN H40", "BOLTORN H311", "BOLTORN H2003", "BOLTORN H2004", "BOLTORN P500", "BOLTORN P501", and "BOLTORN P1000" manufactured by Perstorp.

[0024] The urethane (meth)acrylate compound usable as the aliphatic urethane (meth)acrylate (B) is a compound having at least two (meth)acryloyloxy groups and at least two urethane structures represented by "-NH-C(=O)O-" in one molecule. Examples of the aliphatic urethane (meth)acrylate compound include EBECRYL (registered trademark) 4201, 8402, and 9270 (all manufactured by Daicel-Allnex Co., Ltd.), CN981NS, CN991NS, and CN996NS (all manufactured by Arkema), UA-TMC1, UA-TMC2, UA-TMC4, and UA-TMC5 (all manufactured by Kyoeisha Chemical Co., Ltd.), and NK Oligo UA-4200 and UA-4400 (all manufactured by Shin-Nakamura Chemical Co., Ltd.). By using these aliphatic urethane (meth)acrylates, a cured product that is resistant to heat yellowing can be obtained. These aliphatic urethane (meth)acrylates can be used alone or in combination of two or more. The term "aliphatic" refers to acyclic or cyclic, non-aromatic carbon compounds.

[0025] The active energy ray-curable resin composition of the present invention may contain a photopolymerization initiator, if necessary.

[0026] Examples of the photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, thioxanthone and thioxanthone derivatives, 2,2'-dimethoxy-1,2-diphenylethan-1-one, diphenyl(2,4,6-trimethoxybenzoyl)phosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone.

[0027] Examples of commercially available products of the other photopolymerization initiators include "Omnirad-1173", "Omnirad-184", "Omnirad-127", "Omnirad-2959", "Omnirad-369", "Omnirad-379", "Omnirad-907", "Omnirad-4265", "Omnirad-1000", "Omnirad-651", "Omnirad-TPO", "Omnirad-819", "Omnirad-2022", "Omnirad-2100", "Omnirad-754", "Omnirad-784", "Omnirad-500", Examples of photopolymerization initiators include Omnirad-81 (manufactured by IGM), Kayacure-DETX, Kayacure-MBP, Kayacure-DMBI, Kayacure-EPA, and Kayacure-OA (manufactured by Nippon Kayaku Co., Ltd.), Baicure-10, Baicure-55 (manufactured by Stouffer Chemical Co., Ltd.), Trigonal P1 (manufactured by Akzo Co., Ltd.), Sandray 1000 (manufactured by Sandoz Co., Ltd.), Deep (manufactured by Upjohn Co., Ltd.), Quantacure-PDO, Quantacure-ITX, Quantacure-EPD (manufactured by Ward Blenkinsop Co., Ltd.), and Runtecure-1104 (manufactured by Runtec Co., Ltd.). These photopolymerization initiators can be used alone or in combination of two or more types.

[0028] The content of the photopolymerization initiator is, for example, preferably in the range of 0.05 to 10 mass %, and more preferably in the range of 0.1 to 5 mass %, in the total of the components other than the solvent of the active energy ray-curable resin composition.

[0029] The photopolymerization initiator can also be used in combination with a photosensitizer.

[0030] Examples of the photosensitizer include amine compounds, urea compounds, sulfur-containing compounds, phosphorus-containing compounds, chlorine-containing compounds, and nitrile compounds.

[0031] In addition, the active energy ray curable resin composition of the present invention may contain, as necessary, a (meth)acrylic compound having a carbonate structure, a (meth)acrylic compound having a cyclic structure, or a (meth)acrylic compound having an alkylene glycol structure. By adding these compounds, the viscosity, refractive index, elastic modulus, etc. of the active energy ray curable resin composition can be effectively adjusted.

[0032] Examples of the (meth)acrylic compound having a carbonate structure include those obtained by reacting a polycarbonate polyol with (meth)acrylic acid and / or a (meth)acrylic acid ester.

[0033] The polycarbonate polyol may be, for example, a reaction product between a compound having two or more hydroxyl groups and a carbonate ester.

[0034] Examples of the compound having two or more hydroxyl groups include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,5-hexanediol, 3-methyl-1,5-pentanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,8-nonanediol, 2-ethyl-2-butyl-1,3-propanediol, 1,10-decanediol, 1,12-dodecanediol, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, trimethylolpropane, trimethylolethane, and glycerin. These compounds can be used alone or in combination of two or more.

[0035] Examples of the carbonate ester include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, propylene carbonate, etc. These compounds can be used alone or in combination of two or more kinds.

[0036] Examples of the (meth)acrylic acid ester include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, methoxypolyethylene glycol mono(meth)acrylate, octoxypolyethylene glycol Cholepolypropylene glycol mono(meth)acrylate, lauroxypolyethylene glycol mono(meth)acrylate, stearoxypolyethylene glycol mono(meth)acrylate, phenoxypolyethylene glycol mono(meth)acrylate, phenoxypolyethylene glycol polypropylene glycol mono(meth)acrylate, nonylphenoxypolypropylene glycol mono(meth)acrylate, nonylphenoxypoly(ethylene glycol propylene glycol) mono(meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, etc. can be used. These (meth)acrylic acid esters can be used alone or in combination of two or more.

[0037] Examples of the (meth)acrylic compound having a cyclic structure include (meth)acrylic compounds having a monocycloalkane structure, a benzene ring, a tricyclodecane structure, a dicyclopentenyl structure, an isobornyl structure, a heterocyclic structure having an oxygen atom as a hetero atom, etc. These compounds can be used alone or in combination of two or more kinds.

[0038] Examples of the (meth)acrylic compound having a monocycloalkane structure include cyclohexyl (meth)acrylate, 1,4-cyclohexanedimethanol monoacrylate, etc. These compounds can be used alone or in combination of two or more kinds.

[0039] Examples of the (meth)acrylic compound having a benzene ring include benzyl (meth)acrylate, phenoxy (meth)acrylate, phenoxyethyl (meth)acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, etc. These compounds can be used alone or in combination of two or more kinds.

[0040] Examples of the (meth)acrylic compound having a tricyclodecane (dicyclopentanyl) structure include dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, dimethylol tricyclodecane di(meth)acrylate, tricyclodecane diol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, etc. These compounds can be used alone or in combination of two or more.

[0041] Examples of the (meth)acrylic compound having a dicyclopentenyl structure include dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, etc. These compounds can be used alone or in combination of two or more kinds.

[0042] Examples of the (meth)acrylic compound having an isobornyl structure include isobornyl (meth)acrylate, isobornyl di(meth)acrylate, etc. These compounds can be used alone or in combination of two or more kinds.

[0043] Examples of the (meth)acrylic compound having a heterocyclic ring structure with an oxygen atom as a hetero atom include cyclic trimethylolpropane formal acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, etc. These compounds can be used alone or in combination of two or more.

[0044] The (meth)acrylic compound having an alkylene glycol structure essentially has one or two (meth)acryloyl groups and an alkylene glycol structure in one molecule. Examples of the alkylene glycol structure include 1,2-ethanediol (ethylene glycol), 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,2-propanediol (propylene glycol), 1,2-butanediol, 1,3-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 3-methyl-1,3-butanediol, 2-methyl-1,3-butanediol, 1,2-hexanediol, ethanol, 1,5-hexanediol, 2,5-hexanediol, 3-methyl-1,5-pentanediol, 2,3-dimethyl-2,3-butanediol, 2-ethyl-2-methyl-1,3-propanediol, 1,2-heptanediol, 2-methyl-2-propyl-1,3-propanediol, 2,4-dimethyl-2,4-pentanediol, 3,6-octanediol, 2,2,4-trimethyl 1,3-pentanediol, 2,5-dimethyl-2,5-hexanediol, 2-ethyl-1,3-hexanediol, 1,2-nonanediol, 1,8-nonanediol, 2,8-nonanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-decanediol, 2,2-diisobutyl-1,3-propanediol, etc. These alkylene glycol structures may be present in one molecule, or may be present in two or more types. Among these, ethylene glycol, propylene glycol, and neopentyl glycol are preferred, since they can provide an active energy ray-curable composition capable of forming a lens having excellent heat resistance.Furthermore, the number of repeating units in the alkylene glycol structure is preferably from 2 to 15, since this gives an active energy ray-curable composition capable of forming a lens having superior heat resistance.

[0045] In addition, examples of commercially available products of the (meth)acrylic compound having the alkylene glycol structure include "Miramer M170", "Miramer M202", "Miramer M210", "Miramer M216", "Miramer M220", "Miramer M222", "Miramer M232", "Miramer M280", "Miramer M282", "Miramer M284", "Miramer M286", "Miramer M2040", "Miramer M231", "Miramer M233", "Miramer M235", "Miramer M281", and "Miramer M283" manufactured by MIWON Co., Ltd.; "NK ESTER A-30G", "NK ESTER A-90G", "NK ESTER A-130G", "NK ESTER AM-30PG", "NK ESTER A-200", "NK ESTER A-400", "NK ESTER A-600", "NK ESTER APG-100", and "NK ESTER APG-200" manufactured by Shin-Nakamura Chemical Co., Ltd. APG-200", "NK Ester APG-400", "NK Ester APG-700", "NK Ester A-PTMG-65", "NK Ester M-20G", "NK Ester M-30G", "NK Ester M-40G", "NK Ester M-90G", "NK Ester M-130G", "NK Ester M-30PG", "NK Ester EH-4E", "NK Ester B-20G", "NK Ester S-12E", "NK Ester 2G", "NK Ester 3G", "NK Ester 4G", "NK Ester 9G", "NK Ester 14G", "NK Ester 3PG", "NK Ester9PG", Kyoeisha Chemical Co., Ltd.'s "Light Ester BC", "Light Ester 130MA", "Light Ester BC", "Light Ester 2EG", "Light Ester 3EG", "Light Ester 4EG", "Light Ester 9EG", "Light Ester 14EG", "Light Acrylate EC-A", "Light Acrylate MTG-A", "Light Acrylate EHDG-AT", "Light Acrylate 130A", "Light Acrylate DPM-A", "Light Acrylate P2H-A", "Light Acrylate P-200A", "Light Acrylate 3EG-A", "Light Acrylate 4EG-A", "Light Acrylate 9EG-A", "Light Acrylate 14EG-A", "Light Acrylate PTMGA-250", Hitachi Chemical Co., Ltd.'s "Fancryl FA-240A", "Fancryl FA-P240A", "Fancryl FA-P270A", "Fancryl FA-PTG9A", "Fancryl FA-400M(100)", "Fancryl FA-240M", "Fancryl FA-PTG9M", Daiichi Kogyo Seiyaku Co., Ltd.'s "New Frontier ME-3, New Frontier ME-4S, New Frontier MPE-600, New Frontier PE-200, New Frontier PE-300, New Frontier PE-400, New Frontier PE-600, New Frontier MPEM-400, New Frontier TEGDMA, Nippon Kayaku Co., Ltd.'s KAYARAD PEG400DA and KAYARAD PEG400DA, Osaka Organic Chemical Industry Ltd.'s Viscoat #190, Viscoat #MTG, MPE400A, MPE550A, and Viscoat #310HP.

[0046] Furthermore, the active energy ray-curable resin composition of the present invention may contain, as necessary, urethane (meth)acrylate, epoxy (meth)acrylate, acrylic (meth)acrylate, and the like that are not included in the component (B).

[0047] Furthermore, the active energy ray-curable composition of the present invention may further contain other additives in addition to the components (A) and (B) as necessary.

[0048] Examples of the other additives include additives such as polymerization inhibitors, surface conditioners, antistatic agents, defoamers, viscosity modifiers, light stabilizers, weather stabilizers, heat stabilizers, ultraviolet absorbers, antioxidants, leveling agents, organic pigments, inorganic pigments, pigment dispersants, silica beads, and organic beads; and inorganic fillers such as silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, cerium oxide, and antimony oxide. These other additives can be used alone or in combination of two or more. Among these, it is preferable to add a heat stabilizer and an antioxidant because they can improve heat resistance and moist heat resistance.

[0049] Examples of the heat resistance stabilizer include ethanethiol, 2-methylpropane-2-thiol, n-dodecanethiol, 2,3,3,4,4,5-hexamethylhexane-2-thiol, 2-mercaptoethanol, 4-mercapto-1-butanol, methyl mercaptoacetate, methyl 3-mercaptopropionate, 2-ethylhexyl 3-mercaptopropionate, 3-methoxybutyl 3-mercaptopropionate, n-octyl 3-mercaptopropionate, stearyl 3-mercaptopropionate, 3-(trimethoxysilyl)propane-1-thiol, 3 -(Triethoxysilyl)propane-1-thiol, benzenethiol, benzylthiol, 3-methylbenzenethiol, 4-methylbenzenethiol, naphthalene-2-thiol, pyridine-2-thiol, benzimidazole-2-thiol, benzothiazole-2-thiol, 1,2-ethanedithiol, 1,2-propanedithiol, 1,3-propanedithiol, 1,4-butanedithiol, 2,3-butanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 1,10-decanedithiol, 2,3-dihydroxy-1, 4-Butanedithiol, 3,6-Dioxa-1,8-octanedithiol, 3,7-Dithia-1,9-nonanedithiol, 1,4-Bis(3-mercaptopropionyloxy)butane, 1,4-Bis(3-mercaptobutyryloxy)butane, Tetraethylene glycol bis(3-mercaptopropionate), 1,2-Benzenedithiol, 1,3-Benzenedithiol, 1,4-Benzenedithiol, 2,3-Diamino-1,4-Benzenedithiol, 4,5-Dimethyl-O-xylenedithiol, Toluene-3,4-dithiol, 4,4'-Biphenyl 1,5-Naphthalenedithiol, 6-(dibutylamino)-1,3,5-triazine-2,4-dithiol, 2-amino-1,3,5-triazine-4,6-dithiol, 6-anilino-1,3,5-triazine-2,4-dithiol, 6-(4'-anilinophenyl-isopropylamino)-1,3,5-triazine-2,4-dithiol, 6-(3',5'-tert-butyl-4'-hydroxyanilino)-1,3,5-triazine-2,4-dithiol, quinoxaline-2,3-dithiol, purine-2,6-dithiol, 1,3,4-Thiadiazole-2,5-dithiol, bis(2-mercaptoethyl)ether, trimethylolethane tris(3-mercaptopropionate), trimethylolethane tris(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptobutyrate), 1,3,5-benzenetrithiol, 1,3,5-triazine-2,4,6-trithiol, tris[2-(3-mercaptoethyl)ether] Examples of the heat stabilizer include compounds having a mercapto group, such as tris[2-(3-mercaptopropionyloxy)ethyl]isocyanurate, tris[2-(3-mercaptobutyryloxy)ethyl]isocyanurate, pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), dipentaerythritol hexakis(3-mercaptopropionate), and dipentaerythritol hexakis(3-mercaptobutyrate). These heat stabilizers can be used alone or in combination of two or more.

[0050] Examples of commercially available heat stabilizers include "Chiokalcol 20" manufactured by Kao Corporation; "Karenz MT PE1", "Karenz MT BD1", "Karenz MT NR1", "TPMB", and "TEMB" manufactured by Showa Denko K.K.; and "TMMP", "TEMPIC", "PEMP", "EGMP-4", "DPMP", "TMMP II-20P", and "PEMP II-20P" manufactured by SC Organic Chemical Co., Ltd.

[0051] The amount of the heat stabilizer used in the active energy ray-curable composition is preferably in the range of 0.01 to 10 parts by mass, more preferably in the range of 0.1 to 5 parts by mass, and particularly preferably in the range of 0.5 to 3 parts by mass, from the viewpoint of obtaining sufficient heat resistance.

[0052] Examples of the antioxidant include phenol-based antioxidants, phosphite-based antioxidants, sulfur-based antioxidants, etc. These antioxidants can be used alone or in combination of two or more kinds.

[0053] Examples of the phenol-based antioxidant include styrenated phenol, 2,6-ditertiary butyl-p-cresol, 2,5-ditertiary butyl hydroquinone, 2,5-ditertiary amyl hydroquinone, 3-(3,5-ditertiary butyl-4-hydroxyphenyl)octadecyl propionate, 2,4-bis(octylthiomethyl)-6-methylphenol, 2,2-methylenebis(6-tertiary butyl-p-cresol), 2,2-methylenebis(6-tertiary butyl-4-ethylphenol), 4,4-butylidenebis(6-tert-butyl-m-cresol), 4,4-thiobis(6-tert-butyl-m-cresol), 2,2-thiodiethylbis[3-(3,5-ditert-butyl-4-hydroxyphenyl)propionate], 1,6-hexanediol bis[3-(3,5-ditert-butyl-4-hydroxyphenyl)propionate], bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate][ethylenebis(oxyethylene)], bis[3-[3 -(tert-butyl)-4-hydroxy-5-methylphenyl]propanoic acid]2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diylbis(2-methylpropane-2,1-diyl), N,N-bis[2-[2-(3,5-ditert-butyl-4-hydroxyphenyl)ethylcarbonyloxy]ethyl]oxamide, N,N-(hexane-1,6-diyl)bis[3-(3,5-ditert-butyl-4-hydroxyphenyl)propanamide], 2,4,6-tris(3,5-ditert-butyl) butyl-4-hydroxybenzyl)mesitylene, 1,3,5-tris(3,5-ditertiarybutyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,1,3-tris(2-methyl-4-hydroxy-5-tertiarybutylphenyl)butane, pentaerythritol tetrakis[3-(3,5-ditertiarybutyl-4-hydroxyphenyl)propionate], diethyl(3,5-ditertiarybutyl-4-hydroxybenzyl)phosphonate, and the like.

[0054] Examples of commercially available phenol-based antioxidants include "IRGANOX 1010", "IRGANOX 1010FF", "IRGANOX 1035", "IRGANOX 1035FF(W&C)", "IRGANOX 1076", "IRGANOX 1076FD", "IRGANOX 1098", "IRGANOX 1135", "IRGANOX 1330", "IRGANOX 1520L", "IRGANOX 245", "IRGANOX 245FF", "IRGANOX 259", and "IRGANOX 3114" manufactured by BASF; "ANTAGE BHT", "ANTAGE DAH", "ANTAGE DBH", "ANTAGE W-300", "ANTAGE W-400", "ANTAGE W-500", "ANTAGE Crystal", "ANTAGE SP", "ANTAGE HP-200", and "ANTAGE Examples of such an agent include "ADK STAB HP-300" manufactured by ADEKA CORPORATION, "ADK STAB AO-20", "ADK STAB AO-30", "ADK STAB AO-40", "ADK STAB AO-50", "ADK STAB AO-50F", "ADK STAB AO-50T", "ADK STAB AO-60", "ADK STAB AO-60G", "ADK STAB AO-80", and "ADK STAB AO-330" manufactured by Sumitomo Chemical Co., Ltd., "SUMILIZER GA-80", "SUMILIZER GP", "SUMILIZER MDP-S", "SUMILIZER WX-R", and "SUMILIZER WX-RC" manufactured by Mitsubishi Chemical Corporation, "Yoshinox BB" manufactured by Johoku Chemical Industry Co., Ltd., and "JC-356" manufactured by Johoku Chemical Industry Co., Ltd.

[0055] Examples of the phosphite-based antioxidant include tris(2-ethylhexyl)phosphite, tridecyl phosphite, triisodecyl phosphite, trilauryl phosphite, tris(tridecyl)phosphite, tri(stearyl)phosphite, diphenyl mono(2-ethylhexyl)phosphite, diphenyl monodecyl phosphite, diphenyl isodecyl phosphite, diphenyl mono(tridecyl)phosphite, triphenyl phosphite, tricresyl phosphite, tris(2,4-ditertiary butylphenyl)phosphite, tris(nonylphenyl)phosphite, tetraphenyl dipropylene glycol diphosphite, 4,4-butylidene bis(3-methyl-6-tertiary butylphenyl ditridecyl phosphite), tetra(C12 to C1 5 alkyl)-4,4-isopropylidenediphenyl diphosphite, 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, 3,9-bis(2,6-ditertiarybutyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, 2,4,8,10-tetrakis(1,1-dimethylethyl)-6-[(2-ethylhexyl)oxy]-12H-dibenzo[d,g][1,3,2]dioxaphosphocin, bis(decyl)pentaerythritol diphosphite, bis(tridecyl)pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, hydrogenated bisphenol A·pentaerythritol phosphite polymer, etc.

[0056] Commercially available products of the phosphite antioxidant include, for example, "IRGAFOS 168" and "IRGAFOS 168FF" manufactured by BASF, and "ADK STAB PEP-8", "ADK STAB PEP-36", "ADK STAB HP-10", "ADK STAB 2112", "ADK STAB 2112RG", "ADK STAB 1178", "ADK STAB 1500", "ADK STAB C", "ADK STAB 135A", "ADK STAB 3010", and "ADK STAB 2112R" manufactured by ADEKA CORPORATION. TPP" manufactured by Johoku Chemical Industry Co., Ltd., and "JP-360", "JP-351", "JP-3CP", "JP-308E", "JPE-308E", "JP-310", "JP-312L", "JP-333E", "JPM-308", "JPM-311", "JPM-313", "JPP-100", "JA-805", "JPH-1200", "JPP-88", "JPE-10", "JPE-13R", "JP-318E", "JPP-2000PT", "JP-650", and "JPH-3800" manufactured by Johoku Chemical Industry Co., Ltd.

[0057] Examples of the sulfur-based antioxidant include didodecyl 3,3-thiodipropionate, ditridecyl 3,3-thiobispropionate, dioctadecyl 3,3-thiodipropionate, and pentaerythritol tetrakis[3-(dodecylthio)propionate].

[0058] Examples of commercially available sulfur-based antioxidants include "IRGANOX PS800FL" and "IRGANOX PS802FL" manufactured by BASF, "ADK STAB AO-412S" and "ADK STAB AO-503" manufactured by ADEKA CORPORATION, "KEMINOX PLS" manufactured by Chemipro Chemical Co., Ltd., and "SUMILIZER TP-D" manufactured by Sumitomo Chemical Co., Ltd.

[0059] The amount of the antioxidant used in the active energy ray-curable composition is preferably in the range of 0.01 to 10 parts by mass, more preferably in the range of 0.1 to 5 parts by mass, and particularly preferably in the range of 0.5 to 3 parts by mass, from the viewpoint of obtaining sufficient heat resistance.

[0060] As the other additives, inorganic fillers are preferably used to adjust the refractive index and thermal expansion coefficient. Examples of the inorganic fillers include silica fine particles, zirconia fine particles, and other fine particles, and each of them can be used independently by one type or by combining two or more types. The particle size of the inorganic filler is preferably 1000 nm or less, more preferably 500 nm or less, and particularly preferably 100 nm or less.

[0061] Examples of commercially available products of the silica fine particles include "Methanol Silica Sol", "MA-ST-M", "MA-ST-L", "IPA-ST", "IPA-ST-L", "IPA-ST-ZL", "IPA-ST-UP", "EG-ST", "NPC-ST-30", "PGM-ST", "DMAC-ST", "MEK-ST-40", "MEK-ST-L", "MEK-ST-ZL", "MEK-ST-UP", "MIBK-ST", "MIBK-ST-L", "CHO-ST-M", "EAT-ST", "PMA-ST", "TOL-ST", "MEK-AC-2140Z", "MEK-AC-4130Y", "MEK-AC-5140Z", "MIBK-AC-2140Z", "MIBK-SD-L", "PGM-AC-2140Y", "PGM-AC-4140Y", and "MEK-EC-2130Y" manufactured by Nissan Chemical Co., Ltd.; KE-E10", "SeaHoster KE-E30", "SeaHoster KE-E150", "SeaHoster KE-W10", "SeaHoster KE-W30", "SeaHoster KE-W50", "SeaHoster KE-P10", "SeaHoster KE-P30", "SeaHoster KE-P50", "SeaHoster KE-P100", "SeaHoster KE-P150", "SeaHoster KE-P250", "SeaHoster KE-S10", "SeaHoster KE-S30", "SeaHoster KE-S50", "SeaHoster KE-S100", "SeaHoster KE-S150", "SeaHoster KE-S250", Shin-Etsu Chemical Co., Ltd.'s "QSG-10", "QSG-30", "QSG-100", "QSG-170", and Admatechs Co., Ltd.'s "Admanano" Examples of such fluoropolymers include "YA010C", "YA050C", and "YA100C", and "DLSB-001" and "DLSB-002" manufactured by Daiken Chemical Co., Ltd.

[0062] Examples of commercially available zirconia fine particles include "ZHR-101", "ZHR-103", and "ZHR-200" manufactured by Daiichi Kogyo Seiyaku Co., Ltd., "Zircostar ZP-153" and "Zircostar HR-101" manufactured by Nippon Shokubai Co., Ltd., "SZR-W", "SZR-M", "SZR-CW", "SZR-CM", "SZR-KM", and "SZR-K" manufactured by Sakai Chemical Industry Co., Ltd., "DLZ-001", "DLZ-007", "DLZ-003U", "DLM-001", and "DLM-002" manufactured by Daiken Chemical Industry Co., Ltd., "ZSL-10A", "ZSL-10T", "ZSL-20N", and "ZSL-00014" manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd., "Zirconeo-Cw" and "Zirconeo-Ck" manufactured by ITEC Co., Ltd., and "TZP-103" manufactured by Taisei Kako Co., Ltd.

[0063] Examples of commercially available products of the other fine particles include titania fine particles such as "TTP-113" and "TTP-1132" manufactured by Taisei Chemical Industry Co., Ltd., barium titanate fine particles such as "DLB-001", "DLB-002", and "DLB-003" manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd., antimony tin oxide fine particles such as "DLAT-001" manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd., and indium tin oxide fine particles such as "DLIT-001" manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd.

[0064] The cured product of the present invention can be obtained, for example, by irradiating the active energy ray curable resin composition with active energy rays. Examples of the active energy rays include ionizing radiation such as ultraviolet rays, electron beams, α rays, β rays, and γ rays. When ultraviolet rays are used as the active energy rays, irradiation may be performed under an inert gas atmosphere such as nitrogen gas, or under an air atmosphere in order to efficiently carry out a curing reaction by ultraviolet rays.

[0065] As a source of ultraviolet light, ultraviolet lamps are generally used from the viewpoints of practicality and economy, and specific examples include low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, gallium lamps, metal halide lamps, sunlight, LEDs, etc.

[0066] The cumulative amount of the active energy rays is not particularly limited, but is preferably 100 to 10,000 mJ / cm 2 and preferably 300 to 8,000 mJ / cm 2 By setting the integrated light amount within the above range, it is possible to suppress poor curing due to an insufficient amount of light, and deterioration of the cured product due to an excessive amount of light.

[0067] The irradiation of the active energy rays may be carried out in one step or in two or more steps.

[0068] The Abbe number vD of the cured product is preferably 53 or more, and more preferably in the range of 55 to 60, from the viewpoint of suppressing chromatic aberration.

[0069] The refractive index nD of the cured product at a wavelength of 589 nm is preferably 1.48 or more, and more preferably in the range of 1.49 to 1.55.

[0070] The laminate of the present invention has a resin layer made of the cured product and an inorganic layer. If necessary, it may also have a substrate.

[0071] The inorganic layer refers to a layer made of an inorganic compound, and generally has functions such as anti-reflection and scratch resistance.

[0072] Examples of the inorganic compound include metal oxides, double oxides, metal nitrides, metal fluorides, double fluorides, silicon oxides, silicon nitrides, and mixtures thereof.

[0073] Examples of the metal include lithium, sodium, magnesium, aluminum, titanium, yttrium, indium, tin, zirconium, niobium, cerium, hafnium, and tantalum.

[0074] When the inorganic layer is used as an anti-reflection film layer, the anti-reflection film layer may be a single layer, or may have a low refractive index layer and a high refractive index layer.In addition, each of the low refractive index layer and the high refractive index layer may be one layer or multiple layers.In addition, the stacking order of the low refractive index layer and the high refractive index layer is not particularly limited.

[0075] Examples of inorganic compounds used in the high refractive index layer include lanthanum titanate (LaTiO 3 ), zirconium oxide (ZrO 2 ), titanium dioxide (TiO 2 ), tantalum oxide (Ta 2 O 5 ), niobium oxide (Nb 2 O 5 ), hafnium oxide (HfO 2 ), cerium oxide (CeO 2 ), yttrium oxide (Y 2 O 3 ), and mixtures thereof.

[0076] The inorganic compound used in the low refractive index layer is, for example, magnesium fluoride (MgF 2 ), silicon dioxide (SiO 2 ), aluminum fluoride (AlF 3 ), and mixtures thereof.

[0077] The inorganic layer may be formed by depositing a film on the surface of the resin layer. The method for depositing the inorganic layer is not particularly limited, and any known method can be used as appropriate, but it is preferable to deposit the inorganic layer by physical vapor deposition (PVD) or chemical vapor deposition (CVD).

[0078] From the viewpoint of consistency and simplification of the film formation process, it is more preferable to use physical vapor deposition (PVD), and examples of the film formation method include vacuum deposition, ion plating, and sputtering.

[0079] The vacuum deposition can be performed by, for example, a resistance heating method, a high-frequency induction heating method, an electron beam heating method, or the like.

[0080] The sputtering may be DC sputtering, RF sputtering, magnetron sputtering, or ion beam sputtering. In addition, it may be a parallel plate target system or a facing target system. In addition, examples of the gas introduced into the vacuum chamber include argon, krypton, oxygen, and nitrogen, and each of them may be used alone or in combination of two or more.

[0081] The thickness of the inorganic layer can be appropriately adjusted depending on the intended function. When the objective is anti-reflection function, the thickness is preferably in the range of 10 nm to 5,000 nm, and from the viewpoint of the film strength and productivity of the inorganic layer, the thickness is more preferably in the range of 100 nm to 2,000 nm, and particularly preferably in the range of 250 nm to 1,000 nm.

[0082] Examples of the substrate include polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyolefin resins such as polypropylene, polyethylene, and polymethylpentene; cellulose resins such as cellulose acetate (diacetyl cellulose, triacetyl cellulose, and the like), cellulose acetate propionate, cellulose acetate butyrate, cellulose acetate propionate butyrate, cellulose acetate phthalate, and cellulose nitrate; acrylic resins such as polymethyl methacrylate; vinyl chloride resins such as polyvinyl chloride and polyvinylidene chloride; polyvinyl alcohol; ethylene-vinyl acetate copolymer; polystyrene; polyamide; polycarbonate. polyimide, polyetherimide, and other polyimide-based resins; norbornene-based resins (e.g., "ZEONOR" manufactured by Zeon Corporation), modified norbornene-based resins (e.g., "ARTON" manufactured by JSR Corporation), cyclic olefin copolymers (e.g., "APEL" manufactured by Mitsui Chemicals, Inc.), and other resin films; semiconductor wafers such as silicon, silicon carbide, silicon nitride, sapphire, aluminum nitride, gallium phosphide, gallium arsenide, indium phosphide, and gallium nitride; and glasses such as quartz glass, borosilicate glass, soda-lime glass, silicate glass, and optical glass (crown glass, flint glass).

[0083] Examples of a method for applying the active energy ray-curable composition of the present invention to the film substrate include die coating, microgravure coating, gravure coating, roll coating, comma coating, air knife coating, kiss coating, spray coating, dip coating, spinner coating, brush coating, solid coating by silk screen, wire bar coating, flow coating, dispenser, inkjet printing, screen printing, offset printing, and the like.

[0084] The lens of the present invention is made of the above laminate.

[0085] Examples of the method for producing the lens include a method in which an active energy ray-curable resin composition is applied onto a wafer or a sensor substrate, and the active energy ray-curable resin composition is cured by irradiating the composition with active energy rays using a mold or the like so as to form a desired shape, and then uncured portions are washed away with an organic solvent, and an inorganic layer is formed on a surface of the cured product of the active energy ray-curable resin composition by physical vapor deposition or the like, and the resulting laminate is cut into a desired shape.

[0086] Examples of the organic solvent include ketone-based solvents such as methyl ethyl ketone, acetone, isobutyl ketone, cyclopentanone, and cyclohexanone; cyclic ether-based solvents such as tetrahydrofuran, dioxolane, and dioxane; ester-based solvents such as methyl acetate, ethyl acetate, and butyl acetate; aromatic solvents such as toluene, xylene, and solvent naphtha; alicyclic hydrocarbon-based solvents such as cyclohexane and methylcyclohexane; alcohol-based solvents such as carbitol, cellosolve, methanol, isopropanol, butanol, and propylene glycol monomethyl ether; and glycol ether-based solvents such as alkylene glycol monoalkyl ether, dialkylene glycol monoalkyl ether, and dialkylene glycol monoalkyl ether acetate. These organic solvents can be used alone or in combination of two or more. EXAMPLES

[0087] The present invention will be specifically described below with reference to examples and comparative examples.

[0088] In the present examples, the weight average molecular weight (Mw) is a value measured by gel permeation chromatography (GPC) under the following conditions.

[0089] Measuring device: Tosoh Corporation HLC-8220 Column: Guard column H manufactured by Tosoh Corporation XL -H + Tosoh Corporation TSKgel G5000HXL + Tosoh Corporation TSKgel G4000HXL + Tosoh Corporation TSKgel G3000HXL + Tosoh Corporation TSKgel G2000HXL Detector: RI (differential refractometer) Data processing: Tosoh Corporation SC-8010 Measurement conditions: Column temperature 40℃ Solvent Tetrahydrofuran Flow rate 1.0ml / min Standard: Polystyrene Sample: 100 μl of tetrahydrofuran solution containing 0.4% by mass of resin solids filtered through a microfilter

[0090] (Synthesis Example 1: Production of hyperbranched polymer compound (A-1) having acryloyl groups) In a reaction vessel equipped with a partial condenser, a thermometer, and a stirring rod, 134 parts by mass of trimethylolpropane, 2,500 parts by mass of dimethylolpropionic acid, and 15 parts by mass of paratoluenesulfonic acid were charged and stirred at 100°C to obtain a homogeneous liquid mixture melt. Next, 100 parts by mass of toluene was poured in, and the temperature was raised to 140°C, and water generated while refluxing toluene was distilled out of the system by azeotropy. Next, the reaction was continued for 3 hours at 140°C, and then toluene was distilled out of the system to obtain a hyperbranched polyester polyol (a). The weight average molecular weight of the hyperbranched polyester polyol (a) was 1,800.

[0091] Next, 100 parts by mass of hyperbranched polyester polyol (a), 80 parts by mass of acrylic acid, 0.26 parts by mass of methoquinone, 1.70 parts by mass of paratoluenesulfonic acid, and 120 parts by mass of toluene were charged into a reaction kettle equipped with a partial condenser, a thermometer, and a stirring rod, and water was removed from the system by azeotropy while refluxing toluene at a reaction temperature of 110°C. Next, after continuing the reaction at 110°C for 5 hours, the reaction mixture was neutralized with a 20% by mass aqueous sodium hydroxide solution and washed three times with saline. Finally, toluene was distilled under reduced pressure to remove it from the system, and a hyperbranched polymer compound (A-1) having an acryloyl group was obtained. The weight average molecular weight of this hyperbranched polymer compound (A-1) having an acryloyl group was 2,600. In addition, the average number of functional groups was 18.

[0092] (Example 1: Preparation of active energy ray-curable resin composition (1)) In a 200 mL brown bottle, 35 parts by mass of the hyperbranched polymer compound (A-1) having an acryloyl group obtained in Synthesis Example 1, 20 parts by mass of polyethylene glycol diacrylate ("A-400" manufactured by Shin-Nakamura Chemical Co., Ltd.), 45 parts by mass of an aliphatic urethane acrylate ("EB8402" manufactured by Daicel-Allnex Corporation), and 1 part by mass of a photopolymerization initiator ("Runtecure1104" manufactured by Runtech Chemical Co., Ltd.) were mixed and heated at 60°C for 30 minutes to dissolve uniformly and degassed, thereby obtaining an active energy ray-curable composition (1).

[0093] (Example 2: Preparation of active energy ray-curable resin composition (2)) In a 200 mL brown bottle, 35 parts by mass of the hyperbranched polymer compound (A-1) having an acryloyl group obtained in Synthesis Example 1, 65 parts by mass of an aliphatic urethane acrylate ("UA-TMC4" manufactured by Kyoeisha Chemical Co., Ltd.), and 1 part by mass of a photopolymerization initiator ("Runtecure1104" manufactured by Runtech Chemical Co., Ltd.) were mixed, and the mixture was heated at 60°C for 30 minutes to dissolve uniformly and degassed, thereby obtaining an active energy ray-curable composition (1).

[0094] (Example 3: Preparation of active energy ray-curable resin composition (3)) In a 200 mL brown bottle, 35 parts by mass of the hyperbranched polymer compound (A-1) having an acryloyl group obtained in Synthesis Example 1, 65 parts by mass of an aliphatic urethane acrylate ("UA-TMC5" manufactured by Kyoeisha Chemical Co., Ltd.), and 1 part by mass of a photopolymerization initiator ("Runtecure1104" manufactured by Runtech Chemical Co., Ltd.) were mixed, and the mixture was heated at 60°C for 30 minutes to dissolve uniformly and degassed, thereby obtaining an active energy ray-curable composition (1).

[0095] (Comparative Example 1: Preparation of active energy ray-curable resin composition (4)) In a 200 mL brown bottle, 100 parts by mass of the hyperbranched polymer compound (A-1) having an acryloyl group obtained in Synthesis Example 1 and 1 part by mass of a photopolymerization initiator (Runtecure 1104 manufactured by Runtech Chemical Co., Ltd.) were mixed, heated at 60°C for 30 minutes to dissolve uniformly, and degassed to obtain an active energy ray curable resin composition (4).

[0096] The active energy ray-curable resin compositions obtained in the above Examples and Comparative Examples were used to carry out the following evaluations.

[0097] [Refractive index measurement method] The active energy ray-curable compositions obtained in the Examples and Comparative Examples were poured into a triangular prism mold (thickness 5 mm, length of each side 10 mm) and exposed to 3,000 mJ / cm using a belt conveyor type ultraviolet irradiation device (120 W metal halide lamp) manufactured by iGraphics Co., Ltd. 2 The triangular prism was then irradiated with ultraviolet light of 1000 nm to produce a triangular prism. The refractive indexes of the resulting triangular prism at 25°C were measured using a Kalnew precision refractometer "KPR-3000" manufactured by Shimadzu Corporation, for the d-line, F-line, and C-line. The refractive index of the cured product (n d ) closest to the refractive index (n d ) was appropriately selected and used.

[0098] [How to calculate the Abbe number] Using the refractive indexes of the d line, F line, and C line measured in the above [Method of measuring refractive index], the Abbe number (ν d ) was calculated.

[0099]

number

[0100] [Transmittance measurement method] The active energy ray-curable compositions obtained in the Examples and Comparative Examples were dropped onto a glass plate that had been subjected to a release treatment with octadecyltrichlorosilane, and shim plates with a thickness of 1 mm were placed on the left and right of the oil droplet as spacers, and then the oil droplet was sandwiched between two glass plates that had also been subjected to a release treatment with octadecyltrichlorosilane. The oil droplet of the active energy ray-curable composition sandwiched between the two glass plates was exposed to irradiation intensity of 50 mW / cm using a UV-LED irradiation device "LHPUV365 / 2501" manufactured by Iwasaki Electric Co., Ltd. 2 , cumulative light intensity 8000mJ / cm 2 The resulting coin-shaped cured product was heated in a fan oven at 100°C for 20 minutes, and the initial transmittance at a wavelength of 410 nm was measured using a JASCO V-770 UV-Vis-NIR spectrophotometer.

[0101] [Method for measuring transmittance after heat resistance test] The coin-shaped cured products measured by the transmittance measurement method were (1) heated at 175°C for 10 minutes in a fan oven, and then the transmittance at a wavelength of 410 nm was measured using a JASCO Corporation UV-Visible-Near-Infrared Spectrophotometer "V-770" as the transmittance after heat resistance test 1. The heating temperature was set to 175°C in accordance with the reflow process of low-temperature melting solder and normal melting solder.

[0102] [Method of evaluating cracks after reflow processing] The active energy ray-curable compositions obtained in the examples and comparative examples were dropped onto a cover glass that had been subjected to an adhesion treatment using a silane coupling agent "KBM-5103" manufactured by Shin-Etsu Chemical Co., Ltd., and shaped by a lens replica. After that, the active energy ray-curable compositions were irradiated with a UV-LED irradiation device "LHPUV365 / 2501" manufactured by Iwasaki Electric Co., Ltd. at an irradiation intensity of 50 mW / cm. 2, cumulative light intensity 450mJ / cm 2 After the lens replica was released from the mold, a development process was carried out with propylene glycol monomethyl ether to remove the uncured resin composition. 2 After the main curing was performed by the above method, post-baking was performed for 90 minutes at 100°C using a blower oven to obtain a wafer-level lens. The obtained wafer-level lens was then subjected to sputtering using a Shimadzu Corporation three-target magnetron sputtering device "HSR-522" with a target SiO 2 Sputtering was performed under the conditions of argon gas, gas flow rate of 15 sccm, room temperature of 25°C, and sputtering time of 40 min, to obtain a laminate in which a silicon oxide thin film having a thickness of 0.5 μm was laminated on the surface of the cured product. The surface of the laminate was observed with a microscope "VHX900" manufactured by Keyence Corporation, and the initial appearance of the laminate was evaluated according to the following criteria. Next, after heat treatment at 175°C for 5 minutes using a blower oven, the surface of the laminate was observed with a microscope "VHX900" manufactured by Keyence Corporation, and the appearance of the laminate after heat resistance was evaluated according to the following criteria. ◯: No cracks were observed in the sputtered film. ×: Cracks occurred in the sputtered film.

[0103] [Method of evaluating cracks after humidity and heat resistance test] A wafer-level lens was produced in the same manner as in the lens production procedure described in the evaluation method for cracks after reflow treatment, and a wafer-level lens was obtained. The obtained wafer-level lens was subjected to a moist heat resistance test for 200 hours at a temperature of 85°C and a relative humidity of 85% using an environmental tester (SH-222 manufactured by Espec). After the test, the lens was observed using a microscope "VHX900" manufactured by Keyence Corporation and a laser microscope "OLS5000" manufactured by Olympus Corporation, and evaluated according to the following criteria.

[0104] 5: No cracks were observed in the sputtered film. 4: A crack occurred in the sputtered film. 3: 2 to 5 cracks occurred on the sputtered film. 2: 6 to 10 cracks occurred on the sputtered film. 1: More than 10 cracks occurred in the sputtered film.

[0105] [Table 1]

[0106] From the evaluation results in Table 1, it is clear that the cured products formed from the active energy ray-curable compositions of the present invention in Examples 1 to 3 have high Abbe numbers and high heat yellowing resistance, and have crack resistance even after reflow treatment and moist heat resistance tests. Furthermore, the lens samples of Examples 1 to 3 were free of warping, cracks, or fissures after curing, and had good appearances.

[0107] On the other hand, Comparative Example 1 is an example of an active energy ray curable composition that does not contain the component (B) defined in the present invention, but cracks occurred after reflow treatment, and it was confirmed that the crack resistance was insufficient. Also, Comparative Example 2 is an example of an active energy ray curable composition that does not contain the component (A) defined in the present invention, but cracks occurred after reflow treatment, and it was confirmed that the crack resistance was insufficient.

Claims

1. A lens comprising a laminate having an inorganic layer and a resin layer made of a cured product of an active energy ray-curable resin composition comprising: a hyperbranched polymer compound (A) having a hyperbranched structure and six or more (meth)acryloyl groups in one molecule; and an aliphatic urethane (meth)acrylate (B).

2. 2. The lens according to claim 1, wherein the hyperbranched polymer compound (A) is at least one selected from the group consisting of compounds having a dendrimer structure, compounds having a hyperbranched structure, and compounds having a star structure.

3. 3. The lens according to claim 1, wherein the cured product has an Abbe number vD of 53 or more.

4. 3. The lens according to claim 1, wherein the refractive index nD of the cured product at a wavelength of 589 nm is 1.48 or more.

Citation Information

Patent Citations

  • Urethane (METH)acrylate, method for producing the same, cross-linked urethane (METH)acrylate, method for producing the same, and photocurable aqueous emulsion

    JP2012149224A

  • Curable composition, cured product and laminate

    JP2016190998A

  • Hard coating composition and hard coating film using the same

    JP2017206699A

  • Photosensitive resin composition, cured film and production method of the same

    JP2019117259A

  • Resin composition for optical molding

    JP2019183006A